Ensaios de tratabilidade de água utilizando a casca de tamarindo como coagulante - Santos, Guilherme Silva Amorim dos (Universidade Federal Rural do Semi-Árido, 2018)
The study has great impact in the environmental area, since it comes with the purpose of reducing chemical agents present in the sludge of the water treatment plants, thus not contaminated the environment where this sludge will be destined to its end as well as in the reduction of expenses that an ETA can obtain with the consumption of the conventional coagulant. The objective of this work was to study the water treatability tests with the exchange of the conventional aluminum sulphate coagulant by the tamarind bark that can be obtained from the Tamarindeiro. With the help of the literature, Brazilian standards and based on observations of laboratory tests, highlighting the flocculation and decantation station that occurs in a water treatment plant, were analyzed in tanks designed and developed for this purpose, but at scale smaller. The effluent from the same source was collected and analyzed three times in the same test station, alternating only the coagulant, in order to obtain significant comparisons. Thus, the aluminum sulfate, the tamarind bark and the mixture between the aluminum sulfate and the tamarind bark together were analyzed, in order to obtain considerable results and the search for improvement in the water treatment plants. It was soon possible to conclude that the Tamarind peel and its adsorption capacity are capable of acting as coagulants in a water treatment plant.
Keywords: Tratamento de água; Resíduos de fruta; Estação de decantação; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA